Simulation of current using a two-dimensional numerical model in the Aceh Barat Daya waters, Indonesia. (December 2018) - Rizal, S; Setiawan, I; Boihaki, B; Haditiar, Y; Iskandar, T; Sugianto, S
Abstract: The waters of Aceh Barat Daya are located in the southwest of the province of Aceh, Indonesia. These waters is influenced by the monsoon because these waters are part of the Indian Ocean. The motivation of this research is to simulate the current with 2 D numerical model. Current simulations are performed during the Monsoon (April) transition period from 2014-2016 by using wind data obtained from ECMWF. The wind direction comes from the west. According to this simulation, the pattern of ocean currents is directed to southeast direction. This corresponds to Ekman's theory.